A Mathematical Model of Chopped Miscanthus Briquetting Process. (2015) - Voicea, Iulian; Voicu, Gheorghe; Cârdei, Petru; Vlăduţ, Valentin; Biriş, Sorin
Abstract: This article presents the experimental results of working regime and products obtained from chopped Miscanthus in order to ensure a high energetic capitalization of this plant. The technological system of obtaining briquettes of powdery Miscanthus compressed and at the same time, their qualities are presented. At the same time, notations on Miscanthus briquettes behavior during the time are made. A formula, expressing the quality of product obtained in terms of working process characteristics, is given. Presented material offers suggestions and new directions of continuing the experiments on improving the technological process and briquettes quality.